Evaluation Of Changes in Lumbar Intervertebral Foramina Dimensions in Egyptian Adults by Radiological Study (International Journal of Environmental Sciences, 2025)
OBJECTIVES: Chronic low back pain is a common cause of disability and poor quality of life. Its prevalence increases linearly from the third decade of life until the 60 years of age, being more prevalent in women. Lumbar disc herniation (LDH) is one of the main etiologies seen in 20% of the patients. Although most of the cases can be managed with the conservative treatments, surgery is still needed for those with progressive neurological deficits. Transforaminal percutaneous endoscopic lumbar discectomy (PELD) is done through the Kambin triangle. Morphological changes of lumbar intervertebral foramina are not only important in aiding PELD procedure but also in illustrating stenosis.METHODS: 50 healthy adult subjects (17 males and 33 females) aged between 20-60 years were included in the study. The subjects were outpatient individuals checking themselves after simple injuries. All the cases of fractures, disc prolapse, disc herniation, severe vertebral column deformity were excluded. The gross radiological anatomy of the lumbar region was carefully examined to study various patterns of lumbar intervertebral foramina dimensions. Sectional radiological anatomy of these foramina was analyzed using MRI. The sample size calculation was performed using the STATA 10 program.RESULTS: Significant differences were found at all vertical diameter of intervertebral foramina in all lumber levels was more in males than in females, significant differences were found at vertical diameter of the age group (< 35) was more than age group (> 35) at the following levels L2-L3 and L4-L5 and high significant differences in L2-L3 and in L4-L5.CONCLUSION: This study contributes on elucidating the impacts of gender, age, and anatomical symmetry on intervertebral foramina measurements. These findings highlight the importance of personalized assessment in spinal healthcare, as anatomical variations are associated with different clinical outcomes and risk factors.